The development of Android-based learning media using Kodular in making suit patterns subject - Fitri Nurjanah; Sri Emy Yuli Suprihatin (Jurnal Pendidikan Vokasi, 2023)
This research aims to produce Android-based interactive learning media by utilizing the Kodular application for learning materials for making suit patterns for XII grade students of Fashion Management Vocational Schools. This research uses the research and development model of the Puslitjaknov Team, which consists of five development stages, namely: (1) Analysis of the product produced; (2) Making the initial product; (3) Expert validation and revision; (4) Small-scale trial; and (5) Large-scale trial. This study collected data through observation, questionnaires, and documentation. The test subjects in this development research were students of class XII of Fashion Management of SMK Negeri 2 Godean, with a total of 10 people for small-scale trials and 27 people for large-scale trials. In this study, quantitative descriptive analysis was used to analyze the data. Based on the assessment of material experts and media experts, small-scale trials, and large-scale trials, the findings of this study reveal that the learning media for making Android-based suit patterns are considered valid and practical for use in the classroom. This media is feasible to use to improve students' thinking skills and support students in learning independently, as well as flexible in its application. This media functions well and provides relevant information to students regarding suit pattern making, increasing students' interest in learning, creativity, and learning motivation. The Android-based suit pattern making learning media developed is more efficient than traditional learning media because it can improve learning outcomes by improving the quality of student learning and making it more fun.